KARAKTERISTIK KEPRIBADIAN KONSELOR DALAM TOKOH PEWAYANGAN PUNTADEWA - Caraka N. B, Rahadian Bagus; Zuhdi, M. Sholihuddin (UIN Sunan Kalijaga Yogyakarta, 2022)
Counseling is the process of supporting a counselor (client) counselor with the goal of resolving the problems the counselor is experiencing. To support successful counseling, counselors need to pay attention to their personality competencies. These personality competencies are considered important to support the counseling process. However, the commonly used personality traits of advisors are the personality traits of effective advisors who come from abroad and have a different cultural sensibilities than Indonesia. The main purpose of this study is to identify and explain the character of Puntadewa, and the results of identifying and explaining the character of Puntadewa can be used as a reference for Indonesian consultants to develop effective consultant characteristics. To be able to use it. About local culture. The research method used by researchers is qualitative. The type of study used is library study. The results of this study show that there are six personality traits that can be derived from the Puntadewa doll character that can be used as a reference for Indonesian counselors based on local wisdom. (2) Courtesy; (3) Fairness; (4) Wise; (5) Honesty. (6) Simple; (7) patient. Keywords: Characteristics, Counselor, Puntadewa.